The Establishment Of Indonesian Islamic Parties Post Independence - Muchamad Ifan Maulana; Iin Wahyu Mahmuda; Nasikhin; Fihris; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2023)
Towards Indonesia's independence, the Islamic leaders at that time were not concerned with the establishment of a state based on Islam, but the most important thing was Indonesian independence. This was because the thoughts of the Islamic leaders at that time were based on the population of the Indonesian people who were mostly Muslim, according to which the majority Muslim population would certainly form an Indonesian state based on Islam and a Muslim government. In other words the thinking at that time was that after independence Indonesia would automatically become a country based on Islam.' Another thing that has become an obstacle in the establishment of an Islamic state is that in the historical arena of Muslims, the ideal to establish an Indonesian state based on Islam is not an easy thing to realize. This is due not only to the challenges emanating from the Islamic parties themselves, but also the emergence of secular national parties which have become an obstacle.